2012
DOI: 10.1016/s2221-1691(12)60112-9
|View full text |Cite
|
Sign up to set email alerts
|

Science behind cisplatin-induced nephrotoxicity in humans: A clinical study

Abstract: The present study demonstrates that, acute nephrotoxicity was observed in patients with different types of cancers undergoing cisplatin based chemotherapy due to electrolyte disturbances, when no corrective measures were initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 6 publications
4
39
0
1
Order By: Relevance
“…Serum sodium increased by 1.35% in one study, but other electrolytes showed moderately decreased levels. 16 This was attributed to adequate hydration with normal saline during each cycle of chemotherapy. In an Indian Tertiary care hospital based study, 17 hypocalcaemia was the only abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Serum sodium increased by 1.35% in one study, but other electrolytes showed moderately decreased levels. 16 This was attributed to adequate hydration with normal saline during each cycle of chemotherapy. In an Indian Tertiary care hospital based study, 17 hypocalcaemia was the only abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is in contrast to research conducted by Arankumar et al, (2012) in which the value of creatinine serum increased significantly from BUN value after undergoing cisplatin chemotherapy. This might indicate the possibility of severe nephrotoxicity [12]. The contrasting result obtained by this research compared to other literature resources might be triggered by the lack of sufficient samples to provide significant statistics.…”
Section: Creatinine Serum Value Differential Testmentioning
confidence: 58%
“…Besides that, BUN value is also affected by liver because liver is responsible for the conversion of amino acid into urea [3]. [12]. On the other hand, research conducted by Tazcan et al (2013) involving 52 cancer patients that have undergone platinum-based chemotherapy shows a significant increase in BUN value (p<0.05) after going through cisplatin chemotherapy (Tazcan et al, 2013).…”
Section: Bun Value Differential Testmentioning
confidence: 99%
“…45.71% patients experienced nephrotoxicity in the PAtreated group, whereas the incidence of nephrotoxicity in NPA-treated group was found to be 13.33%. A statistically significant difference was found in the incidence of nephrotoxicity between PA and NPA-treated group (p=0.0064) [3,12].…”
Section: Discussionmentioning
confidence: 91%
“…Frequency and severity of nephrotoxicity induced by platinum-based chemotherapy may be reduced by slow intravenous electrolyte infusions and maintaining the hydration before, during and immediately after the administration of PAs, especially cisplatin [12].…”
Section: Discussionmentioning
confidence: 99%